A printable porous optical film and its preparation method and application
The preparation of porous optical films through screen printing technology solves the problems of complex preparation processes and high cost in the prior art, and realizes low-cost and easy-to-scale production optical films, which are suitable for a variety of fields and improves the efficiency of solar cells.
Patent Information
- Application Number
- CN202210659508.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-10
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-06-10
AI Technical Summary
The preparation process of existing optical films is complex, costly, and difficult to be easily produced on a large scale, making it difficult to compatible with the process requirements of certain fields such as printable solar cells.
The slurry is prepared by mixing nanoparticles, cellulose and terpineol, and the slurry is brushed on the substrate by screen printing, and the cellulose is removed by heating to prepare a porous optical film. The porosity and refractive index of the film are adjusted by adjusting the cellulose content and the type of nanoparticles in the slurry.
It realizes low cost and easy to produce optical films on a large scale, and can continuously adjust the refractive index of the films on a large scale, which is suitable for a variety of fields. At the same time, by adjusting the thickness and refractive index of the film, optical films with different functions can be prepared, such as optical anti-reflection films, reflectance-enhancing films, etc., which improves the photoelectric conversion efficiency of solar cells.
Smart Images

Figure CN115117179B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of optical films, and more specifically, relates to a printable porous optical film and a preparation method and application thereof. Background Art
[0002] Since optical thin films can regulate spectrum and light intensity, they have important applications in various fields, such as glass windows, optical lenses, mobile phone screens, solar cells, etc. Existing optical thin films are usually made by electron beam deposition, atomic layer deposition, magnetron sputtering, chemical etching, dip coating (sol-gel method), thermal evaporation, spin coating, nanoimprinting, self-assembly and other methods. The preparation process is complex, the cost is high, and it is not easy to scale up production.
[0003] Although there are currently a variety of methods and processes for preparing optical films, due to process limitations, most optical films have limited sources of raw materials, high preparation process costs, and are not conducive to large-scale production, especially in some fields (such as printable solar cells), where the preparation processes are incompatible.
[0004] It can be seen that the existing technology has technical problems such as complex preparation process, high cost and difficulty in large-scale production. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a printable porous optical film and a preparation method and application thereof, thereby solving the technical problems of the prior art such as complex preparation process, high cost and difficulty in large-scale production.
[0006] To achieve the above object, according to one aspect of the present invention, a method for preparing a printable porous optical film is provided, comprising:
[0007] The nanoparticles, cellulose and terpineol are mixed to obtain a slurry, and the slurry is brushed on a substrate by screen printing;
[0008] The substrate of the printing paste is heated to remove cellulose therein, thereby obtaining a porous optical film;
[0009] By adjusting the content of cellulose in the slurry, the porosity of the porous optical film is changed, and then the refractive index of the porous optical film is adjusted.
[0010] As the cellulose content in the slurry increases, the porosity of the porous optical film increases, and the refractive index of the porous optical film decreases; as the cellulose content in the slurry decreases, the porosity of the porous optical film decreases, and the refractive index of the porous optical film increases.
[0011] Furthermore, the preparation method further comprises:
[0012] By adjusting the types of nanoparticles in the slurry, the refractive index of the porous optical film can be adjusted without changing the porosity of the porous optical film.
[0013] Furthermore, the preparation method further comprises:
[0014] The thickness of the porous optical film can be adjusted by changing the number of layers of the slurry or the concentration of the slurry screen-printed on the substrate.
[0015] Furthermore, the nanoparticles are at least one of SiO2, ZrO2, TiO2, Ta2O5, Al2O3, ZnO, ZnS, SnO2, TeO2, Y2O3, MgO, WO3, MgF2, and CeO2 nanoparticles.
[0016] Furthermore, the cellulose is at least one of ethyl cellulose, hydroxypropyl cellulose and polyethylene glycol.
[0017] Furthermore, the refractive index of the material selected for the substrate is greater than the refractive index of air, and the refractive index of the material selected for the substrate can be greater than or less than the refractive index of the porous film according to different requirements. To prepare an anti-reflection film, the refractive index of the material selected for the substrate is less than the refractive index of the porous film, and to prepare an anti-reflection film, the refractive index of the material selected for the substrate is greater than the refractive index of the porous film.
[0018] Furthermore, the particle size of the nanoparticles is 5nm-200nm, and preferably, the particle size of the nanoparticles is 20nm-30nm.
[0019] Furthermore, the mass ratio of the nanoparticles, cellulose and terpineol in the slurry is 1:(0.25-4):(20-140), preferably, the mass ratio of the nanoparticles, cellulose and terpineol in the slurry is 1:(1-2):(60-80).
[0020] According to another aspect of the present invention, a printable porous optical film is provided, wherein the porous optical film is prepared by a method for preparing a printable porous optical film.
[0021] According to another aspect of the present invention, an application of a printable porous optical film is provided, wherein the porous optical film is prepared by a method for preparing a printable porous optical film, and during the preparation, an optical anti-reflection film, an anti-reflection film, an infrared filter film, an ultraviolet filter film, a spectroscopic film, a light-passing film in different wavelength ranges, a light-blocking film in different wavelength ranges or a polarizing film is formed by adjusting the thickness or refractive index of the porous optical film, so as to be applied to different fields to meet different needs.
[0022] According to another aspect of the present invention, an application of a printable porous optical film is provided. When the porous optical film is applied to a solar cell, the porous optical film is prepared by a method for preparing a printable porous optical film. During the preparation, the porosity of the porous optical film is increased by increasing the cellulose content in the slurry, thereby reducing the refractive index of the porous optical film. The resulting porous optical film is an optical anti-reflection film.
[0023] According to another aspect of the present invention, an application of a printable porous optical film is provided. When the porous optical film is applied to a solar cell, the porous optical film is prepared by a method for preparing a printable porous optical film. During the preparation, nanoparticles with a low refractive index are used to prepare a slurry. The refractive index of the porous optical film is reduced without changing the porosity of the porous optical film. The resulting porous optical film is an optical anti-reflection film.
[0024] According to another aspect of the present invention, there is provided an application of a printable porous optical film, wherein the porous optical film is used in preparing light-transmitting glass.
[0025] The nanoparticles, cellulose and terpineol are mixed to obtain a slurry, and the slurry is brushed on glass by screen printing;
[0026] The glass with the printed paste is heated to remove the cellulose therein, thereby obtaining a light-transmitting glass with a porous optical film attached thereto;
[0027] By adjusting the cellulose content in the slurry, the porosity of the porous optical film is changed, the refractive index of the porous optical film is adjusted, and then the transmittance of the light-transmitting glass is adjusted.
[0028] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:
[0029] (1) In the present invention, nanoparticles are used as skeleton materials, cellulose is used as pore-forming agent, and pinene alcohol is used as dispersion liquid to mix into slurry. The slurry has good stability and can be stored for a long time. The cost of raw materials and preparation process is low. Moreover, the large-scale production of thin films can be easily achieved through screen printing, which can further reduce the preparation cost and make it more widely used. According to the effective medium theory, after two materials are mixed, their effective refractive index will change. For dielectrics (insulating materials), the effective refractive index of material C obtained by uniformly mixing materials A and B will be n C =pn A +(1-p)n B , where n C is the refractive index of the mixed material C, n A and n Bare the refractive indices of the constituent materials A and B of the mixed material, respectively, and p is the volume ratio of material A in the mixed material C. The refractive index of nanoparticles is greater than that of air, and the porous optical film is a mixed material of skeleton material and air, so its refractive index is lower than that of the skeleton material. The refractive index of the porous material can be adjusted by adjusting the volume ratio of air in the porous optical film (i.e., porosity). The larger the air volume ratio, the lower the refractive index. The preparation method of this optical film is simple, there are many types of optional materials, the raw materials are widely available, the refractive index of the film can be continuously adjusted over a large range, and the scope of use is extremely wide.
[0030] (2) The present invention can also adjust the refractive index of the porous material by adjusting the refractive index of the skeleton material. The higher the refractive index of the skeleton material, the higher the refractive index of the porous material. The refractive indexes of different materials are generally different. For example, at a wavelength of 550nm, the refractive index of SiO2 is about 1.48, the refractive index of TiO2 is 2.5-2.7, and the refractive index of ZrO2 is about 2.0. Therefore, the porous films prepared using different materials have different refractive indices even when the porosity is the same. This makes it possible to change the refractive index of the porous film by changing the raw materials used to prepare the slurry to achieve the desired effect.
[0031] (3) By changing the slurry concentration to change the thickness of the film, it can be applied to substrates with different refractive indices to form optical films with different functions. By changing the mass ratio of raw materials and pinene alcohol, that is, changing the slurry concentration, the content of nanoparticles per unit volume of the slurry can be reduced. The slurry is printed using the same process parameters to form a film. After drying, the solvent pinene alcohol evaporates to form a film. The film obtained by printing with a low concentration of slurry has a lower content of nanoparticles per unit volume, so the film thickness of the obtained film will be lower, so that the thickness of the film can be changed by adjusting the slurry concentration.
[0032] (4) According to the Fresnel formula in optical theory, Where n0 and n1 are the refractive indices of the media on both sides of the interface, and R is the interface reflectivity. The optical reflection of the interface comes from the mismatch of the refractive indices of the media on both sides of the interface. Therefore, inserting a material with a refractive index value between the incident medium and the output medium will have a certain anti-reflection effect. Based on this, the refractive index of the material selected for the substrate is greater than the refractive index of air, and the refractive index of the material selected for the substrate can be greater than or less than the refractive index of the porous membrane according to different requirements.
[0033] (5) The present invention can adjust the refractive index and thickness of the film through screen printing technology. If the optical film is designed and prepared according to the corresponding requirements, optical films with different functions can be prepared for application in different fields. The present invention increases the porosity of the porous optical film by increasing the content of cellulose in the slurry, thereby reducing the refractive index of the porous optical film. The porous optical film formed is an optical anti-reflection film. Applying the optical anti-reflection film to solar cells can reduce the loss of incident light and effectively improve the photoelectric conversion efficiency of solar cells. The refractive index of glass is about 1.52, and the refractive index of air is 1. Printing a porous optical film on glass will be able to achieve a certain anti-reflection effect, making its transmittance higher. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a schematic diagram of preparing a printable porous optical film provided by an embodiment of the present invention;
[0035] Figure 2 is a schematic diagram of a printable porous optical film provided by an embodiment of the present invention;
[0036] Figure 3 is the refractive index curve of the porous SiO2 film provided in Example 1 of the present invention;
[0037] Figure 4 is the refractive index curve of the porous SiO2 film provided in Example 2 of the present invention;
[0038] Figure 5 is the refractive index curve of the porous SiO2 film provided in Example 3 of the present invention;
[0039] Figure 6 is the refractive index curve of the porous SiO2 film provided in Example 4 of the present invention;
[0040] Figure 7 is a cross-sectional SEM photograph of the porous SiO2 film provided in Example 5 of the present invention;
[0041] Figure 8 is a cross-sectional SEM photograph of the porous SiO2 film provided in Example 6 of the present invention;
[0042] Fig. 9 is a cross-sectional SEM photograph of the porous SiO2 film provided in Example 7 of the present invention;
[0043] Fig.10 is a comparison chart of transmittance curves of FTO glass with and without printed porous SiO2 film provided in Example 7 of the present invention;
[0044] Fig.11 is the refractive index curve of the porous TiO2 film provided in Example 8 of the present invention;
[0045] Fig.12 is a comparison chart of transmittance curves of FTO glass with and without printed porous TiO2 film provided in Example 8 of the present invention;
[0046] Fig.13 is the refractive index curve of the porous ZrO2 film provided in Example 9 of the present invention;
[0047] Fig.14 It is a comparison chart of transmittance curves of FTO glass with and without printed porous ZrO2 film provided in Example 9 of the present invention. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0049] like Figure 1 As shown, a method for preparing a printable porous optical film comprises:
[0050] The nanoparticles, cellulose and terpineol are mixed to obtain a slurry, and the slurry is brushed on a substrate by screen printing;
[0051] The substrate of the printing paste is heated to remove cellulose therein, thereby obtaining a porous optical film;
[0052] By adjusting the content of cellulose in the slurry, the porosity of the porous optical film is changed, and then the refractive index of the porous optical film is adjusted.
[0053] Figure 1 In the figure, the brush is a screen printing machine, and from top to bottom are the slurry brushed on the substrate, the substrate and the platform for placing the substrate.
[0054] The preparation method of the present invention is specifically:
[0055] (1) mixing nanoparticles, cellulose and terpineol to prepare a slurry by ball milling or sand milling;
[0056] (2) brushing the slurry onto the substrate by a screen printing machine;
[0057] (3) Place the substrate coated with the slurry on a flat surface for 1-2 hours, and then place it on a hot plate at 70-80 degrees to dry (different slurries can be printed according to different needs);
[0058] (4) Sintering the dried film at a high temperature of 300-500 degrees (depending on the material) for 20-60 minutes to remove the pore-forming agent (cellulose) therein, thereby obtaining a porous optical film.
[0059] The invention adopts the screen printing method to prepare the optical film, the film has good stability and optical performance, simple preparation process, low cost, easy large-scale production, and is applicable to various fields.
[0060] Figure 2 The porous optical film prepared by the preparation method of the present invention is Figure 2 From top to bottom, there are a porous optical film and a platform for placing the film. The porous optical film prepared by the present invention is an insulating material or a semiconductor material, not a conductor.
[0061] The present invention forms a porous film by heating a screen printing stock paste, wherein the stock paste is composed of raw materials (nanoparticles forming the porous film, i.e. the skeleton material mentioned above), cellulose and pine alcohol, and after high-temperature sintering, the cellulose volatilizes away, thereby leaving holes in the film to form a porous film, thereby achieving the purpose of reducing the refractive index of the material. The more cellulose content in the slurry of the printed film, the more holes will be left in the film after high-temperature sintering, that is, the more air content in the porous material, the larger the air volume ratio, and then according to the formula, the refractive index of the porous film will also be lower, therefore, the air volume ratio (porosity) in the porous film can be adjusted by adjusting the content of cellulose in the slurry, thereby changing the refractive index of the film.
[0062] The optical film of the present invention has a simple preparation method, a wide variety of optional materials, a wide range of raw materials, and a film refractive index that can be continuously adjusted over a wide range (the film porosity is adjusted by changing the cellulose content in the slurry to achieve the effect of adjusting the film refractive index), and has a wide range of applications. In addition, the slurry has good stability and can be stored for a long time, the cost of raw materials and preparation process is low, and the large-scale production of the film can be easily achieved through the screen printing method, which can further reduce the preparation cost and make it more widely used.
[0063] The preparation method of the present invention can be used to prepare an optical anti-reflection film, and the film can be applied to a solar cell to reduce incident light loss and improve the photoelectric conversion efficiency of the solar cell.
[0064] When the preparation method of the present invention is used to prepare a double-layer film, nanoparticles, cellulose and terpineol are mixed to obtain a slurry, and the slurry is brushed on a substrate by screen printing;
[0065] The substrate of the printing paste is heated to remove cellulose therein, thereby obtaining a porous optical film;
[0066] By brushing two layers of slurry obtained by mixing different nanoparticles on a substrate in sequence, a double-layer film can be obtained. The double-layer film has excellent anti-reflection performance and hydrophobic and self-cleaning properties.
[0067] For example, TiO2 nanoparticles, cellulose and pinene alcohol are mixed to obtain a first slurry, and SiO2 nanoparticles, cellulose and pinene alcohol are mixed to obtain a second slurry. After the first slurry is printed on a substrate by screen printing and dried, the second slurry is continuously printed on the substrate, and then high-temperature annealing is performed to remove the cellulose after drying, thereby preparing a double-layer porous film of TiO2 and SiO2.
[0068] Example 1
[0069] Taking SiO2 nanoparticles with a particle size of 20nm as raw material, nano-SiO2 particles, ethyl cellulose and pine alcohol are added into a sand mill in a certain mass ratio (nano-SiO2: ethyl cellulose: pine alcohol = 1: 0.25: 80), and then an appropriate amount of anhydrous ethanol is added. SiO2 is dispersed by sand milling. The speed of the sand mill is 2000rpm / h, and the sand milling time is 1 hour. The sand milled slurry is passed through a rotary evaporator to remove the anhydrous ethanol, and finally the corresponding SiO2 slurry is prepared and stored at room temperature.
[0070] With FTO glass as the substrate, SiO2 film was prepared by screen printing with prepared SiO2 slurry. First, the FTO glass substrate to be printed with the film was placed in the card slot of the screen printer (glass side facing up), and then an appropriate amount of SiO2 slurry was applied to the screen. The mesh number of the screen used was 250, and the relevant parameters of the screen printer were: screen gap 1.75mm, screen pressure 1.75kg. The film was brushed on the glass surface. After brushing, the substrate with the film was placed on a flat table and spread for two hours to make the film as flat as possible, and then transferred to a hot table at 75 degrees for drying to remove the pine alcohol in the film. Finally, the dried sample was placed on a hot table and calcined at a high temperature of 400 degrees for 40 minutes to remove the ethyl cellulose in the film, to achieve pore formation, and obtain a SiO2 film containing mesopores (2-50nm) inside.
[0071] According to the effective medium theory, the effective refractive index of porous materials is lower than that of bulk materials, and they can be considered as a mixture of air and bulk materials. The effective refractive index of the mixture is n f for:
[0072] n f =pn air +(1-p)n s
[0073] where n fis the effective refractive index of the porous SiO2 film, i.e., the refractive index measured by spectroscopic ellipsometer, n air is the refractive index of air (1), n s is the refractive index of the bulk material, and p is the porosity. Figure 3 The refractive index curve of the printed porous SiO2 film is shown in Figure 2. Figure 3 The n represents the refractive index, and its refractive index at 550nm is 1.127. According to the formula, its porosity can be calculated to be 0.747.
[0074] Example 2
[0075] Taking SiO2 nanoparticles with a particle size of 20nm as raw material, nano-SiO2 particles, ethyl cellulose and pine alcohol are added into a sand mill in a certain mass ratio (nano-SiO2: ethyl cellulose: pine alcohol = 1: 0.5: 80), and then an appropriate amount of anhydrous ethanol is added. SiO2 is dispersed by sand milling. The speed of the sand mill is 2000rpm / h, and the sand milling time is 1 hour. The sand milled slurry is rotary evaporated by a rotary evaporator to remove anhydrous ethanol, and finally the corresponding SiO2 slurry is prepared and stored at room temperature.
[0076] Using FTO glass as the substrate, the SiO2 film is prepared by a screen printer using the prepared SiO2 slurry. First, place the FTO glass substrate to be printed with the film in the card slot of the screen printer (glass side facing up), and then take an appropriate amount of SiO2 slurry on the screen. The mesh number of the screen used is 250, and the relevant parameters of the screen printer are: screen gap 1.75mm, screen pressure 1.75kg. The film is brushed on the glass surface. After brushing, place the substrate with the film on a flat table and spread it out for two hours to make the film as flat as possible, and then transfer it to a hot table at 75 degrees for drying to remove the pinolene in the film. Finally, place the dried sample on the hot table and calcine it at a high temperature of 400 degrees for 40 minutes to remove the ethyl cellulose in the film and achieve pore formation to obtain a SiO2 film containing mesopores (2-50nm) inside. Its refractive index curve is as follows Figure 4 Its refractive index at 550nm is 1.123, and its porosity can be calculated to be 0.755 according to the formula.
[0077] Example 3
[0078] Taking SiO2 nanoparticles with a particle size of 20nm as raw material, nano-SiO2 particles, ethyl cellulose and pine alcohol are added into a sand mill in a certain mass ratio (nano-SiO2: ethyl cellulose: pine alcohol = 1:1:80), and then an appropriate amount of anhydrous ethanol is added. SiO2 is dispersed by sand milling. The speed of the sand mill is 2000rpm / h, and the sand milling time is 1 hour. The sand milled slurry is rotary evaporated by a rotary evaporator to remove anhydrous ethanol. Finally, the corresponding SiO2 slurry is prepared and stored at room temperature.
[0079] Taking FTO glass as the substrate, SiO2 film is prepared by screen printing with prepared SiO2 slurry. First, place the FTO glass substrate to be printed with the film in the card slot of the screen printer (glass side facing up), and then take an appropriate amount of SiO2 slurry on the screen. The mesh number of the screen used is 250, and the relevant parameters of the screen printer are: screen gap 1.75mm, screen pressure 1.75kg. The film is brushed on the glass surface. After brushing, the substrate with the film is placed on a flat table and spread out for two hours to make the film as flat as possible, and then transferred to a hot table at 75 degrees for drying to remove the pinolene in the film. Finally, the dried sample is placed on a hot table and calcined at a high temperature of 400 degrees for 40 minutes to remove the ethyl cellulose in the film, realize pore formation, and obtain a SiO film containing mesopores (2-50nm) inside. Its refractive index curve is as follows Figure 5 As shown, its refractive index at 550nm is 1.140, and its porosity can be calculated to be 0.720 according to the formula.
[0080] Example 4
[0081] Taking SiO2 nanoparticles with a particle size of 20nm as raw material, nano-SiO2 particles, ethyl cellulose and pine alcohol are added into a sand mill according to a certain mass ratio (nano-SiO2: ethyl cellulose: pine alcohol = 1:2:80), and then an appropriate amount of anhydrous ethanol is added. SiO2 is dispersed by sand milling. The speed of the sand mill is 2000rpm / h, and the sand milling time is 1 hour. The sand milled slurry is passed through a rotary evaporator to remove the anhydrous ethanol, and finally the corresponding SiO2 slurry is prepared and stored at room temperature.
[0082] Using FTO glass as the substrate, the SiO2 film is prepared by a screen printer using the prepared SiO2 slurry. First, place the FTO glass substrate to be printed with the film in the card slot of the screen printer (glass side facing up), and then take an appropriate amount of SiO2 slurry on the screen. The mesh number of the screen used is 250, and the relevant parameters of the screen printer are: screen gap 1.75mm, screen pressure 1.75kg. The film is brushed on the glass surface. After brushing, place the substrate with the film on a flat table and spread it out for two hours to make the film as flat as possible, and then transfer it to a hot table at 75 degrees for drying to remove the pinolene in the film. Finally, place the dried sample on the hot table and calcine it at a high temperature of 400 degrees for 40 minutes to remove the ethyl cellulose in the film, achieve pore formation, and obtain a SiO2 film containing mesopores (2-50nm) inside. Its refractive index curve is as follows Figure 6 As shown, its refractive index at 550nm is 1.140, and its porosity can be calculated to be 0.720 according to the formula.
[0083] Example 5
[0084] Taking SiO2 nanoparticles with a particle size of 20 nm as raw material, nano-SiO2 particles, ethyl cellulose and pine alcohol are added into a sand mill according to three mass ratios (nano-SiO2: ethyl cellulose: pine alcohol = 1:1:60), and then an appropriate amount of anhydrous ethanol is added. SiO2 is dispersed by sand milling. The speed of the sand mill is 2000 rpm / h, and the sand milling time is 1 hour. The sand milled slurry is rotary evaporated by a rotary evaporator to remove anhydrous ethanol. Finally, the corresponding SiO2 slurry is prepared and stored at room temperature.
[0085] Using FTO glass as the substrate, SiO2 film is prepared by screen printing with the prepared SiO2 slurry. First, place the FTO glass substrate to be printed with the film in the card slot of the screen printer (glass side facing up), and then take an appropriate amount of SiO2 slurry on the screen. The mesh number of the screen used is 250, and the relevant parameters of the screen printer are: screen gap 1.75mm, screen pressure 1.75kg. The film is brushed on the glass surface. After brushing, the substrate with the film is placed on a flat table and spread out for two hours to make the film as flat as possible, and then transferred to a hot table at 75 degrees for drying to remove the pinolene in the film. Finally, the dried sample is placed on a hot table and calcined at a high temperature of 400 degrees for 40 minutes to remove the ethyl cellulose in the film and achieve pore formation. A porous SiO2 film with mesopores (2-50nm) and a thickness of about 320nm is obtained. The cross-sectional SEM (scanning electron microscope) photo is shown below. Figure 7 shown.
[0086] Example 6
[0087] Taking SiO2 nanoparticles with a particle size of 20 nm as raw material, nano-SiO2 particles, ethyl cellulose and pine alcohol are added into a sand mill according to three mass ratios (nano-SiO2: ethyl cellulose: pine alcohol = 1:1:80), and then an appropriate amount of anhydrous ethanol is added. SiO2 is dispersed by sand milling. The speed of the sand mill is 2000 rpm / h, and the sand milling time is 1 hour. The sand milled slurry is rotary evaporated by a rotary evaporator to remove anhydrous ethanol. Finally, the corresponding SiO2 slurry is prepared and stored at room temperature.
[0088] Using FTO glass as the substrate, the SiO2 film is prepared by a screen printer using the prepared SiO2 slurry. First, place the FTO glass substrate to be printed with the film in the card slot of the screen printer (glass side facing up), and then take an appropriate amount of SiO2 slurry on the screen. The mesh number of the screen used is 250, and the relevant parameters of the screen printer are: screen gap 1.75mm, screen pressure 1.75kg. The film is brushed on the glass surface. After brushing, the substrate with the film is placed on a flat table and spread out for two hours to make the film as flat as possible, and then transferred to a hot table at 75 degrees for drying to remove the pinolene in the film. Finally, the dried sample is placed on a hot table and calcined at a high temperature of 400 degrees for 40 minutes to remove the ethyl cellulose in the film and achieve pore formation. A porous SiO2 film with mesopores (2-50nm) and a thickness of about 240nm is obtained. The cross-sectional SEM (scanning electron microscope) photo is shown below. Figure 8 shown.
[0089] Example 7
[0090] Taking SiO2 nanoparticles with a particle size of 20 nm as raw material, nano-SiO2 particles, ethyl cellulose and pine alcohol are added into a sand mill according to three mass ratios (nano-SiO2: ethyl cellulose: pine alcohol = 1:1:60), and then an appropriate amount of anhydrous ethanol is added. SiO2 is dispersed by sand milling. The speed of the sand mill is 2000 rpm / h, and the sand milling time is 1 hour. The sand milled slurry is rotary evaporated by a rotary evaporator to remove anhydrous ethanol. Finally, the corresponding SiO2 slurry is prepared and stored at room temperature.
[0091] Using FTO glass as the substrate, the SiO2 film is prepared by a screen printer using the prepared SiO2 slurry. First, place the FTO glass substrate to be printed with the film in the card slot of the screen printer (glass side facing up), and then take an appropriate amount of SiO2 slurry on the screen. The mesh number of the screen used is 250, and the relevant parameters of the screen printer are: screen gap 1.75mm, screen pressure 1.75kg. The film is brushed on the glass surface. After brushing, the substrate with the film is placed on a flat table and spread out for two hours to make the film as flat as possible, and then transferred to a hot table at 75 degrees for drying to remove the pinolene in the film. Finally, the dried sample is placed on a hot table and calcined at a high temperature of 400 degrees for 40 minutes to remove the ethyl cellulose in the film and achieve pore formation. A porous SiO2 film with mesopores (2-50nm) and a thickness of about 180nm is obtained. The cross-sectional SEM (scanning electron microscope) photo is shown below. Fig. 9 shown.
[0092] According to the Fresnel formula in optical theory, Where n0 and n1 are the refractive indices of the media on both sides of the interface, and R is the interface reflectivity. The optical reflection of the interface comes from the mismatch of the refractive indices of the media on both sides of the interface. Therefore, inserting a material with a refractive index value between the incident medium and the output medium will have a certain anti-reflection effect. The refractive index of glass is about 1.52, and the refractive index of air is 1. Printing a porous SiO2 optical film on the glass surface of FTO glass will have a certain anti-reflection effect, making its transmittance higher. The transmittance curves of the FTO glass printed with the SiO2 optical film in this embodiment and the FTO glass without the SiO2 optical film are shown in the figure below. Fig.10 As shown, it can be clearly seen that after printing the porous SiO2 film, the transmittance of the FTO glass is improved, and the maximum transmittance is increased from 85% to 89%.
[0093] Example 8
[0094] Use purchased TiO2 slurry with a particle size of 30nm as raw material. The TiO2 slurry contains ethyl cellulose. Take a certain amount of TiO2 slurry and pineol, the mass ratio of TiO2 slurry and pineol is 1:4 (the ratio is adjustable), then put it in an ultrasonic machine for 48 hours to mix it evenly, and finally get TiO2 slurry, which is stored at room temperature.
[0095] Using FTO glass as the substrate, the TiO2 film is prepared by a screen printer using the prepared TiO2 slurry. First, place the FTO glass substrate to be printed with the film in the card slot of the screen printer (FTO side facing up), and then take an appropriate amount of TiO2 slurry on the screen. The mesh number of the screen used is 150, and the relevant parameters of the screen printer are: screen gap 1.75mm, screen pressure 1.75kg. The film is brushed on the FTO surface. After brushing, place the substrate with the film on a flat table and spread it out for two hours to make the film as flat as possible, and then transfer it to a hot table at 75 degrees for drying to remove the pinolene in the film. Finally, place the dried sample on the hot table and calcine it at a high temperature of 500 degrees for 40 minutes to remove the ethyl cellulose in the film and achieve pore formation to obtain a TiO2 film containing mesopores (2-50nm) inside. Its refractive index curve is as follows Fig.11 As shown. At 550nm, its refractive index is 1.40, which is lower than the refractive index of the original TiO2 (2.5-2.7), indicating that the pores in it have successfully reduced its refractive index. The porous TiO2 film was printed on the glass surface of FTO glass, which successfully improved the transmittance of FTO glass and achieved a certain anti-reflection effect, as shown in Figure 1. Fig.12 shown.
[0096] Example 9
[0097] Taking ZrO2 nanoparticles with a particle size of 30nm as raw material, nano ZrO2 particles, ethyl cellulose and pine alcohol are added into a sand mill in a certain mass ratio (nano ZrO2: ethyl cellulose: pine alcohol = 1: 0.5: 80), and then an appropriate amount of glacial acetic acid (to adjust the dispersibility of the slurry) and an appropriate amount of anhydrous ethanol are added. ZrO2 is dispersed by sand milling. The speed of the sand mill is 2300rpm / h, and the sand milling time is 30 minutes. The slurry obtained after sand milling is rotary evaporated by a rotary evaporator to remove anhydrous ethanol. Finally, the corresponding ZrO2 slurry is prepared and stored at room temperature.
[0098] Using FTO glass as the substrate, prepare ZrO2 slurry and use a screen printer to prepare ZrO2 film. First, place the FTO glass substrate to be printed with the film in the card slot of the screen printer (glass side facing up), and then take an appropriate amount of ZrO2 slurry on the screen. The mesh number of the screen used is 250, and the relevant parameters of the screen printer are: screen gap 1.75mm, screen pressure 1.75kg (the parameters of the screen printer are adjustable). After printing with the screen printer, place the FTO glass substrate with the film on a flat table and spread it out for two hours to make the film as flat as possible, and then transfer it to a hot table at 75 degrees for drying to remove the pinolene in the film. Finally, place the dried sample on the hot table and calcine it at a high temperature of 400 degrees for 40 minutes to remove the ethyl cellulose in the film and achieve pore formation to obtain a ZrO2 film containing mesopores (2-50nm) inside. Its refractive index curve is as shown below. Fig.13 As shown. At 550nm, its refractive index is 1.23, which is lower than the refractive index of the original ZrO2 (2.0-2.2), indicating that the pores in it have successfully reduced its refractive index. The porous TiO2 film was printed on the glass surface of FTO glass, which successfully improved the transmittance of FTO glass and achieved a certain anti-reflection effect, as shown in Figure 1. Fig.14 shown.
[0099] In the above-mentioned embodiments, the slurry can be prepared by other materials to obtain optical anti-reflection films of different raw materials, such as nanoparticles such as Ta2O5, Al2O3, ZnO, ZnS, SnO2, TeO2, Y2O3, MgO, WO3, MgF2, and CeO2. The particle size is not limited to 20nm, 30nm, and the film thickness can be adjusted by changing the concentration of the slurry, and the refractive index of the film can be adjusted by changing the mass ratio of the raw material and the ethyl cellulose in the slurry. The film can be deposited together in multiple layers to form an optical film with better performance and wider functions. The film can be sintered once for each layer deposited, or multiple layers (two or more layers) of the film can be deposited and then sintered together. Through the combination of different types of films, optical films with various uses can be formed, such as optical anti-reflection films, anti-reflection films, infrared filter films, ultraviolet filter films, spectroscopic films, bandpass or band-stop films of different wavelength ranges, and polarizing films, etc., so as to be applied to different fields to meet different needs.
[0100] According to optical theory, optical films with different functions can be obtained by adjusting the refractive index and thickness of the film, as well as the stacking method of the films. For anti-reflection films, as long as a layer of film with a refractive index between the substrate material and the incident medium is deposited on the substrate, a refractive index transition can be achieved between the incident medium and the substrate, reducing the reflection of the interface and achieving an anti-reflection effect. According to wave optics theory, when the optical path difference between two beams of light (with the same frequency) is an odd or even multiple of 1 / 4 wavelength, destructive interference and constructive interference can be achieved respectively, achieving anti-reflection and anti-reflection effects. Then, by adjusting the thickness of the printed optical film, anti-reflection and anti-reflection performance can be achieved respectively. For a basic configuration of The film system, where H is a high-refractive-index material with a film thickness of λ / 4, H / 2 represents a film thickness of λ / 8, L is a low-refractive-index material with a film thickness of λ / 4, λ is the reference center wavelength, which is also the center wavelength of the cutoff band, and m is the number of periods of the film system. It can filter out light with shorter wavelengths to form a long-wave pass filter. By alternately depositing such a high-and-low refractive index by screen printing technology, the thickness of the high-refractive-index material and the low-refractive-index material are selected to be 1 / 8 and 1 / 4 of the reference wavelength, respectively, which will enable the preparation of a long-wave pass filter. By adjusting the position of its central wavelength, the wavelength range it transmits can be made to fall in the infrared light region, thus preparing an infrared filter. On the contrary, for a basic configuration of A film system that can filter out long-wavelength photons to form a short-wave pass filter. Similarly, by alternately depositing low-refractive index materials and high-refractive index materials with thicknesses of 1 / 8 wavelength and 1 / 4 wavelength respectively through screen printing technology, a short-wave pass filter can be achieved. By adjusting the position of the reference wavelength, the transmitted wavelength range can be made to fall within the ultraviolet region to form an ultraviolet filter. By combining the short-wave pass filter and the long-wave pass filter, a bandpass or band-stop filter can be achieved. By adjusting the position of the reference center wavelength, the desired range of bandpass or band-stop can be achieved. The bandpass filter can also be made of a basic configuration of |LHL| m The film system is obtained, where L and H represent low-refractive index material and high-refractive index material with a thickness of 1 / 4 wavelength respectively. By adjusting the position of the reference center wavelength, the bandpass within the desired wavelength range can be achieved. Therefore, by depositing materials with alternating high and low refractive indices through screen printing technology, it is possible to prepare a bandpass filter film. In short, the refractive index and thickness of the film can be adjusted through screen printing technology. If the optical film is designed and prepared according to the corresponding requirements, it is possible to prepare optical films with different functions for application in different fields.
[0101] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a printable porous optical film, characterized in that: include: Nanoparticles are used as skeleton materials, cellulose is used as pore-forming agent, and pineneol is used as dispersion liquid, and the mixture is mixed into a slurry, wherein the mass ratio of nanoparticles, cellulose, and pineneol in the slurry is 1:(1-2):(60-80), and the nanoparticles are SiO2 nanoparticles; then, the slurry is brushed on a substrate by screen printing; the substrate brushed with the slurry is placed on a flat table and spread for 1-2 hours, and then placed on a hot table at 70-80 degrees for drying; The dried printed slurry substrate is sintered at a high temperature of 300-500 degrees for 20-60 minutes to remove the cellulose therein, thereby leaving holes in the film to obtain a porous optical film; By adjusting the content of cellulose in the slurry, the porosity of the porous optical film is changed, and then the refractive index of the porous optical film is adjusted, and the obtained porous optical film is an optical anti-reflection film; The refractive index of the material selected for the substrate is greater than the refractive index of air, and the porous optical film is an anti-reflection film, so the refractive index of the material selected for the substrate is greater than the refractive index of the porous optical film.
2. The method for preparing a printable porous optical film according to claim 1, characterized in that: The preparation method further comprises: The thickness of the porous optical film can be adjusted by changing the number of layers of the slurry screen-printed on the substrate or the concentration of the slurry.
3. A method for preparing a printable porous optical film according to claim 1 or 2, characterized in that: The cellulose is at least one of ethyl cellulose, hydroxypropyl cellulose and polyethylene glycol.
4. An application of a printable porous optical film, characterized in that: A porous optical film is prepared according to the method for preparing a printable porous optical film according to any one of claims 1 to 3. During the preparation, an optical anti-reflection film is formed by adjusting the thickness or refractive index of the porous optical film.
5. An application of a printable porous optical film, characterized in that: The porous optical film is applied to solar cells. The porous optical film is prepared according to the method for preparing a printable porous optical film according to any one of claims 1 to 3. During the preparation, the porosity of the porous optical film is increased by increasing the cellulose content in the slurry, thereby reducing the refractive index of the porous optical film. The resulting porous optical film is an optical anti-reflection film.
Citation Information
Patent Citations
Method for growing thin film with continuously adjustable optical constants
CN114277363A
Oxide optical semiconductor paste for screen printing, oxide optical semiconductor porous thin-film electrode and photoelectric conversion element using it, and manufacturing method of oxide optical semiconductor paste for screen printing
JP2007026994A